2020
DOI: 10.21203/rs.3.rs-27665/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cost-Related Medication Nonadherence in Canada: A Systematic Review of Prevalence, Predictors, and Clinical Impact

Abstract: Background Cost-related nonadherence to medications (CRNA) is common in many countries and thought to be associated with adverse outcomes. The characteristics of CRNA in Canada, with its patchwork coverage of increasingly expensive medications, is unclear. Objectives Our objective in this systematic review was to summarize the literature evaluating CRNA in Canada in three domains: prevalence, predictors, and effect on clinical outcomes.Methods We searched MEDLINE, Embase, Google Scholar, and the Cochrane Lib… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…41 Other studies have suggested that higher financial coverage promotes higher use of and financial access to drugs among populations. 1,16,41 In contrast, a more restrictive model of universal drug coverage offers limited access and mixed drug expenditure based on the payer. 1,4,6,16 From a societal perspective (i.e., total use and costs from both private and public plan coverage), the total cost of medications would change if the total use per person changed after OHIP+ coverage or the total costs per medication changed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41 Other studies have suggested that higher financial coverage promotes higher use of and financial access to drugs among populations. 1,16,41 In contrast, a more restrictive model of universal drug coverage offers limited access and mixed drug expenditure based on the payer. 1,4,6,16 From a societal perspective (i.e., total use and costs from both private and public plan coverage), the total cost of medications would change if the total use per person changed after OHIP+ coverage or the total costs per medication changed.…”
Section: Discussionmentioning
confidence: 99%
“…Our study aligns with others that have found that public prescription drug plans that provide noncatastrophic, firstdollar coverage increase use of public coverage for medications. [5][6][7][34][35][36][37][38][39][40][41][42][43] Expanded coverage, on the other hand, may not improve clinical outcomes because access or adherence is not sufficiently improved, or because the benefit of essential medicines is outweighed by the lack of benefit from nonessential or harmful medicines, which would likely reduce cost burdens for many people but would increase costs for governments. 41 Other studies have suggested that higher financial coverage promotes higher use of and financial access to drugs among populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cost is known to be a barrier to accessing medications in Canada. 32 In addition, user fees, copayments or limits on the quantity of subsidized prescriptions create barriers to essential medications and are associated with worse health outcomes in people whose medication use is most likely to be affected by these cost-sharing measures. 33 Beginning Apr.…”
Section: Temporal Trends In Hba 1cmentioning
confidence: 99%
“…3 Numerous research studies conducted on CRNA have reported that economic factors such as high out-of-pocket medication costs, low income, and absence of medication insurance increase the risk of self-reported CRNA. 6,7 At the same time, CRNA has also been associated with several factors that have no links with financial hardship (e.g., physician communication, medication beliefs). 4 A conceptual framework distinct from general medication nonadherence has been proposed specifically for CRNA.…”
mentioning
confidence: 99%